2016
DOI: 10.1016/j.jss.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

FLOW-assisted value stream mapping in the early phases of large-scale software development

Abstract: PostprintThis is the accepted version of a paper published in Journal of Systems and Software. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Ali, N b. (2016) FLOW-assisted value stream mapping in the early phases of large-scale software development. Systems and Software, Access to the published version may require subscription. Journal of AbstractValue Stream Mapping (VSM) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This is known as perspective of concept modeling. In this modeling elicitation of requirements is done for processes, data and behavior of large-scale software projects [22]. This model is also supported by SA/SD view of large-scale software project [23].…”
Section: Related Workmentioning
confidence: 99%
“…This is known as perspective of concept modeling. In this modeling elicitation of requirements is done for processes, data and behavior of large-scale software projects [22]. This model is also supported by SA/SD view of large-scale software project [23].…”
Section: Related Workmentioning
confidence: 99%
“…Standardizing the medication administration process and creating a safe space to facilitate the process successfully reduced interruptions and distractions from all sources (Kavanagh and Donnelly, 2020). A VSM application was proposed by Bin, Petersen, and Schneider (2016), where the combination of VSM and FLOW was evaluated to identify and alleviate information and communication related to challenges in large-scale software development. Baeza-Serrato (2016) proposed an approach called REDUTEX, which is based on theoretical concepts of lean and synchronous manufacturing to help to understand the behaviour of SMEs and to improve the manufacturing process by reducing customer lead times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it continues to be a challenge in the software industry. 13,14 Several studies have suggested the use of function points. However, function points are not commonly used in the industry.…”
Section: Related Workmentioning
confidence: 99%